Subjectivity in post-positivism: brief essay on the difficulty of applying principles (Revista do Tribunal Regional Federal da 3ª Região, 2014)
This paper contributes to the debate between principles and norms, in order to highlight, on the one hand, axiological nature of the principles and, on the other hand, how difficult the abandonment of objective criteria makes on application of law.
Keywords: principles; postpositivism; judicial activism